Emotional dimensions of educational administration and leadership [ - Samier, Eugenie Angele , 1954-; Schmidt, Michele (Routledge, 2009)
Exploring foundational theories for emotional dimensions of educational administration and leadership this collection covers a broad range of topics, such as ethics, personality, social justice, gender discrimination and organisational culture